Investigating the Effectiveness of Collaborative Strategic Reading (CSR) In Enhancing Reading Comprehension of EFL Students Palu, Indonesia - Ermawati Ermawati; Hastini Hastini (Journal of General Education and Humanities, 2023)
This study aimed to determine whether implementing Collaborative Strategic Reading (CSR) could enhance students' reading comprehension. A quasi-experimental design employed pre-test and post-test assessments as measurement tools. The researcher employed purposive sampling and selected a sample of 40 students. The collected test data were then subjected to analysis using the test of paired samples in the SPSS v. 26 for Windows. The findings from the data analysis using the test of paired samples revealed a significant difference in scores between the pretest and posttest for the experiment class. The computed p-value (two-tailed) was 0.002, which falls below the predetermined significance level of 0.05. Consequently, the hypothesis has been accepted. In summary, Collaborative Strategic Reading (CSR) has been implemented, and results demonstrate that it has enhanced the reading comprehension skills of SMA Negeri 5 Palu's 10th-grade science students.